2018
DOI: 10.3390/ma11050716
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth of Porous MnO2 Coatings Prepared on Nickel Foam and Evaluation of Their Electrochemical Performance

Abstract: Porous MnO2 was uniformly electrodeposited on nickel foam in MnSO4 solution, which was applied as the electrode of supercapacitors. The nucleation/growth mechanisms of porous MnO2 were investigated firstly. Then two kinds of electrochemical measuring technologies, corresponding to the cycle voltammetry (CV) and galvanostatic charge-discharge, were adopted to assess the electrochemical performance of MnO2 electrodes. The results demonstrated that the deposition of MnO2 on nickel foam included four stages. Prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…These peaks can be attributed to Ni foam oxidation and reduction. The second redox peak appeared at 0.87 and 0.68 V vs Ag/AgCl, which relate to the oxidation of Mn 2+ to Mn 3+ and reduction of Mn 3+ to Mn 2+ . From the data obtained from CV, the constant potential at 1.1 V for electrodeposition of MnCO 3 was selected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These peaks can be attributed to Ni foam oxidation and reduction. The second redox peak appeared at 0.87 and 0.68 V vs Ag/AgCl, which relate to the oxidation of Mn 2+ to Mn 3+ and reduction of Mn 3+ to Mn 2+ . From the data obtained from CV, the constant potential at 1.1 V for electrodeposition of MnCO 3 was selected.…”
Section: Resultsmentioning
confidence: 99%
“…The second redox peak appeared at 0.87 and 0.68 V vs Ag/AgCl, which relate to the oxidation of Mn 2+ to Mn 3+ and reduction of Mn 3+ to Mn 2+ . 43 From the data obtained from CV, the constant potential at 1.1 V for electrodeposition of MnCO 3 was selected. The potential of 1.1 V was selected because at a higher anodic potential, the Ni foam starts precipitating out and mixing with the electrolyte.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The development of potential power sources to compete with ever-increasing energy demands is a significant worldwide issue . With the growth of the market for portable electronic devices and hybrid electric vehicles, the need for energy storage devices is increasing. , Batteries, fuel cells, and supercapacitors are the most efficient and effective electrochemical energy conversion and storage technologies. Due to various advantages, including environment-friendly, high power density, low cost, and so on, supercapacitors have attracted massive attention in recent research activities in the energy sector. However, supercapacitors have a lower energy density than batteries, and hence increasing their energy density to that of batteries is desirable. , While the performances of supercapacitors are mainly determined by the electrode material rather than the construction mechanism, it is important to develop the most effective electrode materials from available sources using facile routes. , …”
Section: Introductionmentioning
confidence: 99%
“…Reports have been found on the capacitive properties of MnO 2 prepared by different methods. For instance, Huang et al found a capacitive value of 400 F g –1 for MnO 2 synthesized by an electrochemical deposition technique, Xi et al found a value of 200 F g –1 , Wan et al synthesized MnO 2 by chemical precipitation method and obtained a capacitive value of 200 F g –1 , Ali et al developed a powdered nanoflower morphology of MnO 2 by electrowinning and obtained the capacitive value of 294 F g –1 , and Goikolea et al used polyol method to prepare MnO 2 and found capacitance equal to 130 F g –1 . All of the reported values are in the moderate range and still, there is an excellent opportunity to work with enhancing the capacitive performance of MnO 2 (1370 F g –1 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation